2005
DOI: 10.1385/bter:103:3:249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combination of Niacin and Chromium(III)-Chloride on the Skin and Lungs of Hyperlipemic Rats

Abstract: The aim of this study was to investigate the biochemical effects of niacin and chromium(III)-chloride on serum lipid peroxidation, uric and sialic acids, and the extent of lipid peroxidation and glutathione levels in skin and lung tissues of hyperlipidemic rats. In this study, female Swiss albino rats, 12 mo old, were used. They were randomly divided into four groups. Group I animals were fed with a standard pellet diet and water ad libitium. Group II rats were fed with a standard pellet diet and were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…There was a positive correlation between serum cholesterol and LDL, and serum SA, suggesting that the serum SA levels are highly related to serum lipids. In contrast to our findings, in the study of Yanardag et al [16] the significant increase in serum SA levels has been found after a longer treatment period (60 day) by feeding a 2 % cholesterol diet.…”
Section: Effect Of Hypercholesterolemiacontrasting
confidence: 99%
See 2 more Smart Citations
“…There was a positive correlation between serum cholesterol and LDL, and serum SA, suggesting that the serum SA levels are highly related to serum lipids. In contrast to our findings, in the study of Yanardag et al [16] the significant increase in serum SA levels has been found after a longer treatment period (60 day) by feeding a 2 % cholesterol diet.…”
Section: Effect Of Hypercholesterolemiacontrasting
confidence: 99%
“…The results of the present study showed that total cholesterol and LDL levels significantly increased, but HDL and TG levels did not change significantly in experimental hypercholesterolemia induced by 1.63 % cholesterol diet for both 3and 6-week feeding periods. These findings are consistent with those in which hypercholesterolemic diets were containing cholesterol ranging between 0.5 % to 2 %, with or without cholic acid [16,19,20]. Hypercholesterolemia has also been reported to reduce the amount of SA on the surface of certain cells in experimental animals [21,22,23].…”
Section: Effect Of Hypercholesterolemiasupporting
confidence: 87%
See 1 more Smart Citation
“…Our previous studies performed on hyperlipidemic rats documented that hyperlipidemia caused partial damage to the liver and renal tissues. As well, niacin and chromium (III) supplementations could provide a beneficial effect both on the liver structure and biochemistry, as these supplementations have a protective effect against oxidative damage to tongue, lens, spleen and kidney as well as reducing total serum lipid and cholesterol levels (Bolkent et al, 2004;Yanardag et al, 2005;Atac et al, 2006;Sengezer-Inceli et al, 2007). The present study intended to investigate possible damage to the intestinal mucosa of rats fed with a high-fat cholesterol diet and whether or not treatments of niacin and chromium (III) have a protective effect on the intestine of hyperlipidemic rats.…”
mentioning
confidence: 99%
“…The endogenous antioxidant enzymes (e.g SOD, CAT, GR and GSHpx) are responsible for the detoxification of deleterious oxygen radicals (Jacob, 1995). Some trace elements, particularly selenium (Se), zinc (Zn) and chromium (Cr) can support antioxidant function and consequently reduction in mortality in critically ill patients (Yanardag et al, 2005). Se, Zn and Cr are essential trace elements for all organisms, body growth and development (Jain and Kannan, 2001).…”
Section: Introductionmentioning
confidence: 99%